Obstructive sleep apnea: oral appliances and materials - Cheruku, Srilekha; Duggineni, Chalapathi Rao; Harilal, G; Lukka, Pavani (International Journal of Dental Materials, 2021)
For the dental profession in general and in prosthodontists speciality, the subject of sleep medicine continues to offer great challenges and opportunities in diagnosis, treatment planning, and treatment based on qualitative evidence. Though the role contends by the prosthodontists is still in its infancy, there is a lot to find out and understand in the rapidly evolving field of sleep medicine because the recognition of co-managing patients with sleep disorders by the prosthodontists is quick changing into a reality. This article discusses the prosthodontic perspectives, particularly on obstructive sleep apnea.